The Effect of Use of Cow Manure on the Growth of Two Cultivars of Glycine Max L. Using a Verticulture Planting System - Dwina, Silvi; Rahmadina , Rahmadina (Newinera Publisher, 2024)
This study aims to provide data on the verticulture method planting and the use of cow manure to black soybeans (Glycine max L.). This study used a factorial Randomized Block Design (RAK) containing two factorials and four replications. K1 refers to the unit 1 soybean cultivar, while K2 stands for the pearl 2 cultivar. One of the cultivar factors is this (K). Inside the interval (P), we find three values: P1= 0 kg, P2= 0.18 kg, and P3= 0.32 kg. “Among the variables that underwent changes were plant height, leaf count, leaf area index, chlorophyll content, relative growth rate (LPR), net assimilation rate (LAB), and active root nodules. According to the results, there was no significant difference between using 0.16 kg/bed of organic fertilizer or no fertilizer at all when measuring plant height at 7, 14, 21, 28, 35, and 42 HST for Cultivar K1 (detam 1)”. The availability of organic fertilizer at 0.32 kg/bed was significantly affected by manure at 7, 14, 21, 28, 35, and 42 HST at the third dosage. The results of this study show that neither cultivar 1 nor pearl cultivar 2 had any discernible impact on the vegetative development of black soybean plants when manure was applied at dosages of 0 kg, 0.16 kg, and 0.32 kg.